Do one thing : the breakthrough you need for the progress you want - Evans, Geraint (Consultant) (Pearson, 2021)
"This text is designed to get you started so you can begin to feel you are getting closer to being the person you want to be and living the life you want to live. We all feel stuck sometimes. This can be a combination of many factors that, at best, are delaying you or, at worst, are blocking you from getting to your desired destination. We'll work together to figure out practical strategies for addressing ruts in your daily routine, stress, a lack of communication or not knowing where to turn for inspiration"--